Impounded people : Japanese-Americans in the relocation centers - Spicer, Edward Holland, 1906-1983; Hansen, Asael T.; Luomala, Katherine; Opler, Marvin K. (Marvin Kaufmann), 1914-1981 (University of Arizona Press, 2021)
This important final report of the War Relocation Authority, written in 1946 and now released in book form with a comprehensive introduction by Edward H. Spicer, describes the growth and changes in the community life and how attitudes of Japanese-American relocatees and WRA administrators evolved, adjusted, and affected one another on political, social, and psychological levels.